FORAMINIFEROS DANIANOS DE LA FORMACION PEDRO LURO, PROVINCIA DE BUENOS AIRES, ARGENTINA (Ameghiniana, 2013)
Thirty species of Foraminifera from the upper part of Pedro Luro Forrnation (Danian age) Puerto Belgrano n? 20 well, Colorado Basin, Buenos Aires Province, are considered. This fauna includes one new species Baggatella coloradoensis, so that the known geologic range of the genus is extended into the Paleocene.